IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON ORGANIZATION PERFORMANCE - Dr. VIJAYA LAKSHMI POTHURAJU, Dr. P ALEKHYA (International Journal of Advanced Science and Technology, 2020)
This paper aims to present the organization’s performance for socially responsible actions, in Information Technology (IT) sector to contribute to improving the competitiveness of those organizations. The analysis is from different levels of employees working for the organization. It investigates the link among firms ‟relationship with employees with the objective to find out if there is a competitive advantage in applying Corporate Social Responsibilities practices. Besides the direct influence of Corporate Social Responsibility practices on organization performance, quality of work-life has been analyzed. The empirical analysis was constructed on survey data through the Chi-square test. To accomplish this research objective data were collected from a sample of selected IT companies in Hyderabad. Respondents were employees working at different levels in the organizations. The outcome shows that there is a strong connection between corporate Social responsibility practices and organization performance. In addition, the significant relationship in developing Social Responsibilities Practices positively translates, with quality of work life.